Theory of Square-Wave Voltammetry of Two-Step Electrode Reaction Using an Inverse Scan Direction - Milivoj Lovrić; Šebojka Komorsky-Lovrić (International Journal of Electrochemistry)
A theory of square-wave voltammetry of two-step electrode reaction with kinetically controlled electron transfers is developed, and a special case of thermodynamically unstable intermediate is analyzed. If the first reaction step is reversible and the second one is quasireversible, the response splits into two peaks if the scan direction is inverted. The separation of these peaks increases with frequency.